THE EFFECT OF CUSTOMER COMPREHENSION ON BRAND ATTACHMENT WITH EMPHASIS ON BRAND PREFERENCES (CASE STUDY: MELLET INSURANCE COMPANY) - Khosravi, Saber; Yazdani, Naser (Revista Inclusiones, 2019)
Today, most product owners realize that if they want to remain competitive market, they most to gain a competitive advantage over other competitors, thus creating a brand to differentiate. On the other hand, recent research in marketing indicates the importance of bonding and attachment and loyalty in the relationship between the consumer and the brand. Marketing researches in the past decade has check and verify the concept of attachment. Therefore in this study was trying to properly Survey brand equity construct based on the customer and brand attachment and brand preferences of customers in the market And selected evaluation process by study on the effect of the and their relationship to each other, And so Evaluated and tested the effect of customer comprehension on brand attachment with emphasis on brand preferences (case study: Mellat Insurance Company). Based on the framework of research and theoretical foundations of the model and also were collected research data through questionnaires.